Botulinum toxin A injection for post-stroke upper limb spasticity and rehabilitation practices from centers across Asian countries - Rosales, Raymond L.; Chia, Nicholas V. C.; Kumthornthip, Witsanu; Goh, Khean Jin; Mak, Choon Soon; Kong, Keng He; Ng, Yee Sien; Chou, Li Wei; Flordelis, M. Jeanne; Do, Thuy; Maisonobe, Pascal; Li, Leonard S. W.; et al. (Frontiers in Neurology, 2024)
Purpose Describe real-life practice and outcomes in the management of post-stroke upper limb spasticity with botulinum toxin A (BoNT-A) in Asian settings. Methods Subgroup analysis of a prospective, observational study (NCT01020500) of adult patients (≥18 years) with post-stroke upper limb spasticity presenting for routine spasticity management, including treatment with BoNT-A. The primary outcome was goal attainment as assessed using goal-attainment scaling (GAS). Patients baseline clinical characteristics and BoNT-A injection parameters are also described. Results Overall, 51 patients from Asia were enrolled. Rates of comorbid cognitive and emotional problems were relatively low. Patients tended to have more severe distal limb spasticity and to prioritize active over passive function goals. Most (94.1%) patients in the subgroup were treated with abobotulinumtoxinA. For these patients, the median total dose was 500 units, and the most frequently injected muscles were the biceps brachii (83.3%), flexor carpi radialis (72.9%), and flexor digitorum profundus (66.7%). Overall, 74.5% achieved their primary goal and the mean GAS T score after one treatment cycle was 56.0 ± 13.0, with a change from baseline of 20.9 ± 14.3 (p < 0.001). The majority (96.1%) of Asian patients were rated as having improved. Conclusion In the Asian treatment setting, BoNT-A demonstrated a clinically significant effect on goal attainment for the real-life management of upper limb spasticity following stroke.